Japońska Polska. Kulturowy wizerunek Polski w Japonii - Zajączkowski, Ryszard (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The presence of Polish culture in Japan dates back to the early 20th century, but it was only after World War I when translations of the most famous works by Henryk Sienkiewicz, Władysław Reymont and Stefan Żeromski appeared. After that the Polish Franciscans did a lot for popularizing Poland in the thirties and later. After World War II the Japanese had discovered particularly the works of Stanisław Lem, Witold Gombrowicz, Stanisław Witkiewicz (Witkacy) or Bruno Schulz. Their work is promoted, among others, by Tokyo X Theatre. In addition, there was an interest in Polish literature commemorating the war (Jerzy Andrzejewski, Bogdan Wojdowski, Tadeusz Borowski). Some translators who have already died such as Yonekawa Kazuo, Yoshigami Shōzō, Kudō Yukio, and the living ones Sekiguchi Tokimasa and Numano Mitsuyoshi have contributed a lot to the familiarity of Polish literature. Also Tadeusz Kantor put on his plays in Japan. Thanks to Andrzej Wajda’s films, Polish cinema has already won recognition in the fifties. Such Polish directors as Krzysztof Zanussi, Krzysztof Kieślowski, Roman Polański, Jerzy Kawalerowicz are known in Japan as well. Also, the music of Chopin is very popular in Japan. Our cultural canon, however, differs from the one known by the Poles. As noted by Sekiguchi Tokimasa, “Japanese Poland is inevitably different from the Polish Poland.”